Marked - Cast, P. C. (Cast, P. C. House of night, 2007)
The House of Night series is set in a world very much like our own, except in 16-year-old Zoey Redbird's world, vampires have always existed. In this first book in the series, Zoey enters the House of Night, a school where, after having undergone the Change, she will train to become an adult vampire--that is, if she makes it through the Change. Not all of those who are chosen do.